Multi-dimensional electrical impedance myography of the tongue as a potential biomarker for amyotrophic lateral sclerosis. Issue 4 (April 2020) - Alix, James J.P.; McDonough, Harry E.; Sonbas, Buket; French, Sophie J.; Rao, D. Ganesh; Kadirkamanathan, Visakan; McDermott, Christopher J.; Healey, T. Jamie; Shaw, Pamela J.
Highlights: Novel electrical impedance myography system uses electrodes on both surfaces of the tongue. The device produces reliable data, even in inexperienced hands. The results differentiate between healthy and ALS muscle and reveal disease change over time. Abstract: Objective: In amyotrophic lateral sclerosis (ALS) bulbar disease biomarkers are lacking. We evaluated a novel tongue electrical impedance myography (EIM) system, utilising both 2D and 3D electrode configurations for detection of tongue pathology. Methods: Longitudinal multi-frequency phase angle spectra were recorded from 41 patients with ALS (baseline, 3 and 6 months) and 30 healthy volunteers (baseline and 6 months). ALS functional rating scale-revised (ALSFRS-R) data and quantitative tongue strength measurements were collected. EIM data were analysed for reliability (intra-class correlation coefficient; ICC) and differences between patients and volunteers ascertained using both univariate (Mann-Whitney U test) and multivariate techniques (feature selection and L2 norm). Results: The device produced highly reliable data (pooled ICC: 0.836). Significant EIM differences were apparent between ALS patients and healthy volunteers (P < 0.001). EIM data demonstrated a significant relationship to tongue strength and bulbar ALSFRS-R scores (P < 0.015). The EIM recordings revealed a group level longitudinal change over 6 months and consistently identified patients in whom symptoms or tongue strength changed. Conclusions: The novel EIM tongue system produces reliable data and can differentiate between healthy muscle and ALS-related disease. Significance: Tongue EIM utilising multiple frequencies and electrode configurations has potential as a bulbar disease biomarker in ALS.